PENGRAUH WORK LIFE BALANCE DAN LINGKUNGAN KERJA NON FISIK TERHDAP KEPUASAN KERJA KARYAWAN (Studi Kasus Pada PT. Agrecinal Bengkulu Utara) - Zaenal Abidin; Ratnawili Ratnawili (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
This study aims to determine the influence of Work Life Balance and Non-Physical Work Environment on Employee Job Satisfaction. This research uses quantitative research methods. With the population in this study are field employees of PT. North Bengkulu Agricinal, with the sampling method using the Purposive Sampling method in conducting the research the respondents were obtained randomly, totaling 112 people. In this study using data collection methods by way of observation, interviews and distributing questionnaires or questionnaires. The data that has been collected is then processed using an instrument test, analysis of respondents' responses, classic assumption test, multiple linear regression analysis, coefficient of determination (R2) and hypothesis testing using SPSS 25 Based on the results of multiple linear regression, the formulation Y = 3.877 + 0.863X1 + 0.279X2 Coefficient of determination R2 = 0.639 or 63.9% while the remaining 0.361 or 36.1% is influenced by other variables outside the research. work-life balance (X1) obtained that the value of t count for tcount > ttable (9.896 > 1.659) with a significance of 0.000 <0.05. the work environment variable (X2) is 4.961, this means tcount > ttable (4.961 > 1.659) with a significance of 0.000 <0.05. From the results of data processing, it can be concluded that work-life balance and non-physical work environment partially or simultaneously have a positive and significant effect on job satisfaction Keywords: work-life balance, non-physical work environment, job satisfaction